Astrocyte morphology, heterogeneity, and density in the developing African giant rat (Cricetomys gambianus) - Olude, Matthew A.; Mustapha, Oluwaseun A.; Aderounmu, Oluwatunde A.; Olopade, James O.; Ihunwo, Amadi O. (Frontiers in Neuroanatomy, 2015)
Astrocyte morphologies and heterogeneity were described in male African giant rats (AGR) (Cricetomys gambianus, Waterhouse) across three age groups (5 neonates, 5 juveniles and 5 adults) using Silver impregnation method and immunohistochemistry against glia fibrillary acidic protein (GFAP). Immunopositive cell signaling, cell size and population were least in neonates, followed by adults and juveniles respectively. In neonates, astrocyte processes were mostly detected within the glia limitans of the mid and hind brain; their cell bodies measuring 32±4.8 µm in diameter against 91±5.4µm and 75± 1.9µm in juveniles and adults respectively. Astrocyte heterogeneity in juvenile and adult groups revealed eight subtypes to include fibrous astrocytes chiefly in the corpus callosum and brain stem, protoplasmic astrocytes in the cortex and dentate gyrus (DG); radial glia were found along the olfactory bulb (OB) and subventricular zone (SVZ); velate astrocytes were mainly found in the cerebellum and hippocampus; marginal astrocytes close to the pia mater; Bergmann glia in the molecular layer of the cerebellum; perivascular and periventricular astrocytes in the cortex and third ventricle respectively. Cell counts from twelve anatomical regions of the brain were significantly higher in juveniles than in adults (p≤0.01) using unpaired student t-test in the cerebral cortex, pia, corpus callosum, rostral migratory stream (RMS), DG and cerebellum. Highest astrocyte count was found in the DG, while the least count was in the brain stem and sub cortex. Astrocytes along the periventricular layer of the OB are believed to be part of the radial glia system that transport newly formed cells towards the hippocampus and play roles in neurogenesis migration and homeostasis in the AGR. Therefore, astrocyte heterogeneity was examined across age groups in the AGR to determine whether age influences astrocytes population in different regions of the AGR brain and discuss possible functional roles.